Algorithmic Framework For Onthology Mapping And Merging - Kiu, Ching Chieh (2007)
This research proposes OntoDNA, an automated ontology mapping and merging algorithmic framework to provide a scalable environment for interoperating ontologies between information sources. Onto DNA aims to offer contextual and robust ontology mapping and merging through hybrid unsupervised clustering techniques comprising of Formal Concept Analysis (FCA), Self-organization Map (SOM) and K-Means clustering incorporated with lexical measurement, Levenshtein edit distance.